The prognostic value of the neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, and prognostic nutritional index for survival in patients with colorectal cancer - Zhu Xianya; Xu Qiuping; Zhou Yi; Zhu Chunrong; Zeng Lili (Open Medicine)
To analyze the impact of the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), prognostic nutritional index (PNI), and body mass index on the prognosis of colorectal cancer patients and to assess their clinical value. This cohort study included patients who underwent radical resection (R0 resection) for colorectal cancer. Peripheral blood laboratory test results for all patients were obtained within 1 week prior to surgery for the calculation of the NLR, PLR, and PNI. A total of 201 patients were included in the analysis. A total of 19 patients experienced relapse, and 30 patients died. The median follow-up duration was 39.2 months. Receiver operating characteristic curve analysis indicated that the PNI demonstrated moderately high predictive accuracy for overall survival (OS), with an area under the curve of 67.31%. After stratification based on the cutoff value, patients with a PNI of ≥44.48 exhibited a better survival prognosis than those with a PNI of <44.48 (P = 0.001). However, according to the univariate Cox regression analysis, the PNI was significantly associated with OS (hazard ratio: 0.29; 95% confidence interval: 0.14–0.62; P = 0.001). The PNI, rather than the NLR or PLR, exhibited better predictive performance. After classifying patients based on the PNI cutoff value, patients with a high PNI had better survival outcomes.